The Connections Between Ecology and Infectious Disease (Advances in Environmental Microbiology,, 2018)
This book summarizes current advances in our understanding of how infectious disease represents an ecological interaction between a pathogenic microorganism and the host species in which that microbe causes illness. The contributing authors explain that pathogenic microorganisms often also have broader ecological connections, which can include a natural environmental presence; possible transmission by vehicles such as air, water, and food; and interactions with other host species, including vectors for which the microbe either may or may not be pathogenic. This field of science has been dubbed disease ecology, and the chapters that examine it have been grouped into three sections. The first section introduces both the role of biological community interactions and the impact of biodiversity on infectious disease. In turn, the second section considers those diseases directly affecting humans, with a focus on waterborne and foodborne illnesses, while also examining the critical aspect of microbial biofilms. Lastly, the third section presents the ecology of infectious diseases from the perspective of their impact on mammalian livestock and wildlife as well as on humans. Given its breadth of coverage, the volume offers a valuable resource for microbial ecologists and biomedical scientists alike.